Views of University Students on Death Anxiety and Near-Death Treatments - Değirmen, Nuriye (Acta Bioethica, 2021)
The study was planned to evaluate the views of university students about death anxiety and near-death treatments. Between October and December 2018, the Andel Khalek death anxiety scale and the survey questions were applied to 742 university students. 66% of the participants are female. The Cronbach Alpha values of the dimensions were found to be 0.909 for fear of dead body cemetery, 0.820 for fear of terminal illness, and 0.724 for fear of post-mortem. The death anxiety score of women was higher than that of men. The majority of the participants stated that death was associated with distressing social conditions and psychological problems. They are undecided about the usefulness of drug treatments and individual autonomy. A relationship was found between these statements and the death anxiety scale dimension scores. The majority of them stated that there should be qualified treatments, the importance of providing economic opportunities, and that gender discrimination should not be made. In the study, it was concluded that university students have death anxiety and are sensitive to end-of-life treatments. It is suggested that their anxiety can be reduced with health education, improvement of social conditions and psychological support.